Optimizing POF/PCF based optical switch for indoor LAN - Bhuiyan, Moinul; Rashid, Muhammad Mahbubur; Ahmed, Sayem; Bhuiyan, Munira; Kajihara, Masanori (IOP Publishing, 2013)
For indoor local area network (LAN) the Polymer optical fiber (POF) is mostly appropriate, because of its large core diameter and flexible material. A 1×2 optical switch for indoor LAN using POF and a shape memory alloy (SMA) coil actuator with magnetic latches was successfully fabricated and tested. To achieve switching by the movement of a POF, large displacement is necessary because the core diameter is large (e.g., 0.486mm). A SMA coil actuator is used for large displacement and a magnetic latching system is used for fixing the position of the shifted POF. The insertion loss is 0.40 to 0.50dB and crosstalk is more than 50dB without index-matching oil. Switching speed is less than 1s at a driving current of 80mA. A cycling test was performed 1.4 million times. Polymer clad fiber optical (PCF) switch also fabricated and tasted.